Necrobusiness - Krusenstjerna, Fredrik von; Solarz, Richard (Sweden, 2008)
Verzio FF The Polish newspaper Gazeta Wyborcza unearthed a remarkable story in the Polish city of Łódź. Dead patients were apparently worth more than living ones. Investigative journalist Monika Sieradzka traveled with two Swedish documentary filmmakers, Fredrik von Krusenstjerna and Richard Solarz, to Poland's second largest city to find out who was involved in the mysterious deaths of ambulance patients. No-one wanted to talk until local pathologist Jacek Tomalski was arrested for trying to murder prominent funeral director Witold Skrzydlewski. Using the testimonies of both parties, the documentary reveals a scheme to corner the market on funerals and burials by bribing paramedics to deliver bodies only to Skrzydlewski's funeral homes. The scheme seems foolproof, until other local funeral homes find out about it and want to get in on the action. Necrobusiness is a chilling investigation into a business partnership gone awry – full of corruption, betrayal, blackmail, and murder.